THE PALAEOBIOGEOGRAPHY OF SILURIAN RAMPHOPRIONID POLYCHAETE ANNELIDS - Eriksson M. (My University, 2002)
Silurian palaeobiogeography of the Ramphoprionidae (Annelida; Polychaeta) is outlined. Members of the family are reported from northern Europe (Estonia, Sweden and England), the Russian Arctic (Severnaya Zemlya), and the Canadian Arctic (Baillie–Hamilton Island). These areas were located fairly close to the palaeoequator during the Silurian and a faunal exchange is indicated by the broad, intercontinental distribution of the family. A few taxa may, however, have been endemic. Ramphoprionids had long stratigraphical ranges and were generally fairly rare during the Silurian, infrequently exceeding ten per cent of the jawed polychaete faunas.
Keywords: Silurian; Paleozoic::Silurian; Палеозой::Силурийская